The effect of transmitted Er:YAG laser energy through a dental ceramic on different types of resin cements - Tak, Onjen; Sari, Tugrul; Malkoc, Meral Arslan; Altintas, Subutayhan; Usumez, Aslihan; Gutknecht, Norbert (My University, 2015)
Background and ObjectiveThe laser debonding procedure of adhesively luted all-ceramic restorations is based on the ablation of resin cement due to the transmitted laser energy through the ceramic. The purpose of this study was to determine the effect of Er:YAG laser irradiation transmitted through a dental ceramic on five different resin cements.